As normas de defesa do consumidor brasileiras e seus impactos nas redes de eletrodomésticos gaúchas - Baccin, Dirceu (Universidade do Vale do Rio dos Sinos, 2015)
This study examines the impacts of Brazilian consumer protection standards, based on Economic Analysis of Law, before the home appliance retailers, suppliers and consumers. The study aims to bring economic approach to public policies and examines the need for constant government intervention in the Brazilian consumer law. The labor approach had a qualitative focus exploratory in nature, which will provide support for further research theme, to further approach the Economic Analysis of Law with the Law of the Brazilian consumer. The main results of the research indicate that the Brazilian consumer protection standards brought as economic impacts increased sales, consequent regulation of the market and the envisaged legal certainty and increased internal bureaucracy and business costs, which in part are passed on to consumers and manufacturers.
Keywords: Análise econômica do direito; Direito do consumidor; Redes varejistas de eletrodomésticos; Intervenção do Estado; Economia e direito; Custos de transação; Liberalismo; Economic analysis of law; Consumer law; Retailers of home appliances; State intervention; Economics and law; Transaction costs; Liberalism; ACCNPQ::Ciências Sociais Aplicadas::Administração